Simulation and Optimization of Optical Amplifiers in Optical Communication Networks - Surinder Singh (My University, 2008)
For several years now, optical fiber communication systems are being extensively used all over the world for telecommunication, video and data transmission purposes. Fiber optics has made a revolutionary change in commercial telecommunications over the past few decades. The demand for transmission over the global telecommunication network will continue to grow at an exponential rate and only fiber optics will be able to meet the challenge. Multimedia optical networks are the demands of today to carry out large information like real time video services. Presently, almost all the trunk lines of existing networks are using optical fiber. This is because the usable transmission bandwidth on an optical fiber is so enormous (as much as 50 THz) as a result of which, it is capable of allowing the transmission of many signals over long distances. However, attenuation is the major limitation imposed by the transmission medium for long-distance high-speed optical systems and networks. So with the growing transmission rates and demands in the field of optical communication, the electronic regeneration has become more and more expensive. The powerful optical amplifiers came into existence, which eliminated the costly conversions from optical to electrical signal and vice versa. Due to the need of longer and longer unrepeated transmission distances and ultra fast broadband transmission, the advanced transmission schemes have to be investigated. So, it is imperative to investigate into the feasibility of unrepeated transmission and ultra fast broadband transmission over long distances. In order to achieve these goals i.e. broadband and repeaterless transmission of an optical communication system, it is of utmost importance to optimize the optical amplifier and have placement in optical networks. The semiconductor optical amplifiers (SOAs) have attracted much attention as they are cost effective as compared to erbium doped fiber amplifiers for long haul optical communication system. The semiconductor optical amplifiers (SOAs) have wide gain spectrum, low power consumption, ease of integration with other devices and low cost. But as gain saturation problem arises in multichannel optical system, it limits the system performance. This thesis is mainly concerned with the use of optical amplifiers (SOAs and EDFAs) in multichannel wavelength division multiplexing (WDM) optical communication system iv and network. The aim of investigation is to increase the transmission distance, flexibility and cascadability of optical networks by optimizing optical amplifiers (SOAs, EDFAs). The cascaded utilization of the semiconductor optical amplifier (SOA) is not possible for long transmission distance due to gain saturation problem which arises from cross gain modulations (XGM), cross phase modulation (XPM) and four wave mixing (FWM) etc. Therefore, these nonlinearities of SOA produce crosstalk and power penalty problems in long haul WDM optical communication system. In order to utilize the SOA for long haul WDM transmission link, the structural optimization is performed by developing the SOA model based on the analysis for multichannel WDM optical communication system. Therefore it is essential to optimize structural parameters of SOA in order to reduce the power penalty and bit error rate problem which arises due to gain saturation. The optimization is made by simulation of multichannel WDM optical transmission link with cascaded SOA. The effect of amplified spontaneous emission (ASE) noise is also minimized for adequate amplification factor. It is observed that differential phase shift keying (DPSK) system has large capacity as compared to on off keying (OOK) system by using cascaded optimizing SOA for 1050 km transmission distance. The simulative optimization of confinement factor and differential gain is done for reducing cross gain modulation of SOA for improving transmission distance at 40 Gb/s and 80 Gb/s. The soliton RZ-DPSK WDM signals with high capacity up to 0.4 Tb/s is transmitted up to a distance of 4550 km successfully by using optimized semiconductor optical amplifiers with spectral efficiency of 0.4 bit/s/Hz. It is observed from the XPM analysis that by increasing the carrier lifetime, width and thickness while reducing confinement factor, differential gain and bias current in the SOA structure, mitigate the crosstalk due to the cross phase modulations. It is shown that the SOA model obtained on basis of XPM is attractive, when used as pre-amplifiers and in-line amplifier for long haul links up to 5250 km for 10 × 40 Gb/s soliton DPSK WDM signals. These results provide useful information for designing of long WDM transmitter links at higher capacity by using low cost SOA. The placement of SOA is investigated for long haul WDM and DWDM (dense wavelength division multiplexing) transmission of RZ-DPSK signal. It is shown that postpower compensation method is superior than pre- and symmetrical-power compensation methods. By using optimum span scheme based on post-power compensation method, it is possible to transmit ten channels at 10 Gb/s up to transmission distance of 68908 km v for channel spacing of 100 GHz. Further by optimization of the optical phase modulator bandwidth i.e. 5.5 GHz for 400 mA bias current, the maximum transmission distance approaches to 17227 km for 10 × 10 Gb/s DWDM signals for channel spacing of 20 GHz by using same optimum span scheme. The improvement of receiver sensitivity and bandwidth of a SOA pre-amplifier model is developed by reducing ASE noise extremely low i.e. 22.3 μW for 0.1 mW input power. The minimum receiver sensitivity of -69.9 dBm is observed at BER floor of 4.6 × 10-10 for PIN receiver at 10 Gb/s. Also improvement of receiver sensitivity of -19.2 dBm and - 46.5 dBm is observed for PIN receiver and DPSK receiver at 40 Gb/s. It has been shown that the gain variation increases with the increase of input light power and is also observed that tolerance of input wavelength power is more than 100 nm. The SOA optical pre-amplifier is found to be more relaxed from optical alignment and anti-reflection coating and eliminates the need of optical filter. Due to limited bandwidth of the SOA, there is requirement of EDFAs for larger bandwidth optical communication system. We are using different approaches to gain flattening in EDFAs without using additional components i.e. gain flattening filter, dispersion shift fiber and periodic gratings etc. The gain flattening can be achieved by connecting two EDFAs with opposite gain characteristic i.e. peak gain of first EDFA for a given wavelength and another EDFA has a valley gain with same wavelength. The overall power penalty can be reduced by using 3rd pre-amplifier EDFA. Therefore, by using gain flattening approach, the maximum transmission distance up to 490 km can be achieved for sixteen channels at 40 Gb/s with channel spacing of 200 GHz. Another approach by using optical super Gaussian notch filter, the transmission distance is improved up to 504 km for 16 × 40 Gb/s WDM for non return to zero (NRZ) signals. The wavelength converter leads to the increase the cascadability and capacity of future optical networks. The nonlinearities of SOA like four wave mixing (FWM) and cross phase modulation (XPM) is utilized for improving the performance of wavelength converter based on FWM and XPM. The effect of FWM and XPM in SOA is improved by structural parameter optimization of SOA. This can be done in such a manner that the SOA never saturates and produces maximum FWM and XPM signals with minimum gain fluctuations. It is shown that 50 nm up and down wavelength conversion is possible for the NRZ-DPSK by using FWM in SOA. The Q factor improvement observed is 1.74 dB for signal-to-pump ratio of -5 dB at 0 dBm pump signal for 50 nm up converter. Ten stage cascaded wavelength conversion over 1302 km single mode transmission is possible for vi 10 Gb/s NRZ-DPSK by using FWM in the SOA. The wavelength conversion based XPM in the SOA-MZ1 configuration has wide band i.e. more than 15 nm up and down conversions with conversion efficiency more than -9 dB. It is observed that high active region length and bias current in the SOA leads to XPM in the SOA-MZ1 configuration. The performance of optical communication network topologies i.e. bus, ring, star, and tree is compared for 10 Gb/s DPSK signal in the presence of optimized SOA at minimum signal input power. The bus network topology supported maximum 27 users. For ring network topology, the maximum nodes are more than 29. The number of users supported can be increased by decreasing splice and insertion loss in star network topology. It is evaluated that tree network topology offers maximum numbers of users with minimum utilization of optimized SOAs and optical couplers. Therefore, tree network topology in the presence of optimized SOAs provided low cost solution for connecting metropolitan area networks. Therefore, this study establishes the optimization of optical amplifiers in the fiber optical communication networks resulting in the revolutionary growth of internet traffic for terrestrial fiber backbone networks. Also, the number of users and transmission distance can be increased by improving the power budget or reducing the losses in the network by using these optical amplifiers. Most of the research findings of this thesis have been published in various international referred journals (Chapters 2, 3, 4, 5, 6 and 7) as per the list at pages (237-238).
Keywords: optical amplifiers; WDM; SOA; EDFA; Wavelength Connectors